An investigation into the traumatic experiences among Black female characters in Homegoing from a postcolonial perspective - Hu, Jing; Mani, Manimangai; Kaur, Hardev (Sciedu Press, 2024)
Yaa Gyasi‟s debut novel, Homegoing (2016) narrates the struggles of black female characters under structural oppression and the intergenerational transmission of trauma. While previous research has explored oppression and identity, this study explores how trauma gets passed down among black women, examining both victims‟ and perpetrators‟ experiences. Utilizing postcolonial trauma theory and transgenerational trauma concepts, this research aims to identify how oppression manifests and is transmitted among generations of black women. Findings from this study advocate, that there is a need to recognize intergenerational trauma but the past must not silhouette the future and respect for „differences‟ in diverse societies.